Road Perception Based Geographical Routing Protocol for Vehicular Ad Hoc Networks - Kashif Naseer Qureshi; Abdul Hanan Abdullah; Jaime Lloret (International Journal of Distributed Sensor Networks)
Vehicular ad hoc networks (VANETs) are going to be an emerging multihop communication exploit among vehicles to deliver data packets. The special characteristics of vehicular network make the communication link between vehicles unreliable. To handle high mobility and environmental obstacles, most of geographical routing protocols do not consider stable links during packet transmission which lead to higher delay and packet dropping in network. In this paper, we propose road perception based geographical routing protocol named RPGR for VANET. The proposed routing protocol incorporates relative distance, direction, and midrange forwarder node with traffic density to forward the data toward destination in order to improve geographical forwarding between and at the intersections. Simulation results show that the proposed routing protocol performs better as compared to existing solutions.